2000
DOI: 10.1001/archopht.118.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perifoveal Tissue Dissection in the Management of Acute Idiopathic Full-Thickness Macular Holes

Abstract: To evaluate the efficacy of perifoveal tissue dissection (PTD) on patients undergoing pars plana vitrectomy for idiopathic macular holes of less than 1-year's duration.Methods: Pars plana core vitrectomy was performed on 107 eyes of 104 consecutive patients with acute idiopathic macular holes. One cohort had routine PTD. In the other cohort, no attempt was made to strip preretinal tissue. Follow-up was longer than 6 months (follow-up range, 6 to 36 months).Results: Overall, 95 (89%) of all macular holes were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 22 publications
7
50
0
3
Order By: Relevance
“…22 Surgical techniques and outcomes have since improved, and many case series now report primary anatomical closure following conventional surgery in more than 90% of eyes with full-thickness macular holes. [3][4][5][6] Intraocular tamponade agents in macular hole surgery Intraocular tamponade following vitrectomy for macular holes is believed to facilitate reapposition of the rim of detached neurosensory retina and to provide an interface with the vitreous fluid component that serves as a template for a fibrin membrane and glial migration across the macular hole. It is also suggested that the tamponade agent might address intraretinal hydration by preventing subretinal recruitment of vitreous fluid through the hole.…”
Section: Surgical Approaches For Macular Holesmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Surgical techniques and outcomes have since improved, and many case series now report primary anatomical closure following conventional surgery in more than 90% of eyes with full-thickness macular holes. [3][4][5][6] Intraocular tamponade agents in macular hole surgery Intraocular tamponade following vitrectomy for macular holes is believed to facilitate reapposition of the rim of detached neurosensory retina and to provide an interface with the vitreous fluid component that serves as a template for a fibrin membrane and glial migration across the macular hole. It is also suggested that the tamponade agent might address intraretinal hydration by preventing subretinal recruitment of vitreous fluid through the hole.…”
Section: Surgical Approaches For Macular Holesmentioning
confidence: 99%
“…In one nonrandomised comparative series of 107 eyes, an overall closure rate of 89% was achieved with visual acuity improving by 2 lines or more in 85% of eyes; ILM peel was associated with no statistically significant difference in closure rate or visual outcome. 5 While ILM peeling may improve the rate of anatomical closure, evidence suggests that it can result in an adverse effect on visual function. In one series, ILM peel resulted in anatomical closure in 100% of 29 eyes compared to 85.1% of 27 eyes without ILM peel.…”
Section: Peeling Of the Ilmmentioning
confidence: 99%
See 1 more Smart Citation
“…This transparent layer is acellular, composed of collagen closely associated with glycoproteins, and only a few micrometers thick. Several studies have proven the efficiency of ILM-maculorhexis in the treatment of macular holes and epimacular proliferation [1][2][3][4][5]. Recently, ILMremoval has been recommended also for patients with diffuse diabetic macular edema [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Macular hole surgery always involves complete vitreous detachment from the ILM [1][2][3]. This provides the possibility of subsequent selective ILM laser ablation because under such conditions the ILM is not covered by another tissue layer but directly accessible by the laser light.…”
Section: Introductionmentioning
confidence: 99%